Katuk leaf dried noodles (Sauropus androgynus (L) Merr) with different combinations of wheat and banana flour (Musa paradisiaca L.): Mi kering daun katuk (Sauropus androgynus) dengan perbedaan kombinasi tepung terigu dan tepung pisang kepok (Musa paradisiaca L.) - Mifta Ayu Fauziah; Akhmad Mustofa; Vivi Nuraini (Agrobiotek, 2025)
In Indonesia, dry noodles are one of the most widely consumed foods because they are easy to cook. The use of banana flour as a substitute for making noodles is an effort to diversify food in reducing imports of wheat flour. This study dried noodles were made from katuk leaf extract and from the substitution of banana kepok flour with wheat flour. The chemical and organoleptic properties of noodles added with banana kepok flour and katuk leaf extract as natural dyes are the focus of this study. A two-factor factorial Complete Randomized Design (RAL) was used in this study, specifically the ratio of wheat flour to cocoon banana flour (5:95, 10:90, 15:85 g) and the concentration of katuk leaf extract (10/100, 20/100, 30/100 ml). The results showed that katuk leaf dried noodles the ratio of cocoon banana flour and wheat flour 5:95 with katuk leaf extract 30g/100ml contain an ash content of 3.43%; protein content of 14.72%; crude fiber of 11.11%; antioxidant activity of 17.32%; reduced sugar content of 0.24%. The organoleptic test results of dry noodles of katuk leaves compared to banana kepok flour and wheat flour 5:95 with katuk leaf extract 30g/100ml resulted in a stable green color with a score of 2.95 (quite like), aroma 2.52 (strong enough), taste 2.10 (quite like), and overall liking 2.99 (quite like). The highest antioxidant activity parameter was obtained with a ratio of banana kepok flour and wheat flour 15:85 with katuk leaf extract 30g/100ml with a yield of 23.07%. The noodles that the panelists liked the most were the ratio of banana kepok flour and wheat flour 5:95 with katuk leaf extract 30g / 100ml with a result of 2.99 (quite like). Dried noodles made from katuk leaves and banana kepok have high enough antioxidant activity so that they can become nutritious foods that also have beneficial values for body health.